PERSEPSI MASYARAKAT TENTANG PERAN PETANI PEREMPUAN DI DESA SIMPANG KUBU KECAMATAN KAMPAR KABUPATEN KAMPAR - Derry Pelangi; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research i s motivated by the role of women in rice farmingwhich is generally carried out by men but not in the intersection village where the task of taking care of rice farming in the Simpang Kubu village is the role and responsibility of women. The formulation of the problem of this research is